Glomerular Density in the Renal Biopsies of patients with Focal Segmental Glomerulosclerosis: A Single Center Study - Faiz, Muhammad Fahad; Hussain, Mudassar; Afzal, Aurangzeb; Hassan, Usman; Hameed, Maryam; Ishtiaq, Sheeba (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Generally, focal segmental glomerulosclerosis has a poor prognosis. It often progresses to end stage renal disease. Several clinical parameters are under research to define the prognosis and progression of the disease to end stage renal disease so that early treatment is given. Aim: To correlate the glomerular density with different variants of focal segmental glomerulosclerosis and its association with the outcome of a disease. Methods: Retrospective cohort study. Department of Histopathology, ShaukatKhanum Hospital and Research Center, Lahore from 1st January 2018 to 31st December 2020. One hundred and fifty five cases of focal segmental glomerulosclerosis as confirmed first by histology and then by immunofluorescence methods (IHC) and patients were enrolled. The biopsied tissues were embedded in paraffin and cut into 3-4 mm sections. Global glomerulosclerosis was defined when the entire glomerulus was involved in sclerosis, and segmental sclerosis was defined when part of the glomerulus was sclerosed. Interstitial fibrosis was defined when there was increased extracellular matrix separating tubules in the cortical area. Results: The mean glomerular density was 2.2±4. A lower glomerular density (<3/mm2) was associated with higher urinary protein excretion and lower estimated glomerular filtration rate. There were more patients in this group who had hypertension. The lower glomerular density was however, associated with lesser global and segmentally sclerosed glomeruli. More patients (80%) had to undergo either transplant or dialysis.Over half of patients (62.6%) were hypertensive, with only 24.5% receiving dialysis or transplant. Most were treated with medical therapy, with 74% receiving steroids. The mean follow-up time was 24±18 months, and most biopsies showed NOS variants. Almost 21% had remission, while 65% had relapse. Patients with higher glomerular filtration rate (GD) had higher eGFR and UPE. Practical implication: Pakistan’s hilar type of focal segmental glomerulosclerosis (FSGS) has worse outcomes due to its lowest glomerular density. Improving pathology evaluation, training, and knowledge is crucial for prompt diagnosis and treatment. Customizing treatment regimens based on FSGS and glomerular density, improving healthcare resource distribution, and promoting public health campaigns can help prevent end-stage renal disease. Conclusion: Glomerular density is lowest in the hilar type of focal segmental glomerulosclerosis followed by not otherwise specified, tip, and collapsing variants of focal segmental glomerulosclerosis. The lower glomerular density patients have a worse outcome and require dialysis more often. Hence, patients with these variants should be treated more aggressively and their glomerular density can be used for prognosis.